Collected essays on the Greek Bible and Greek lexicography - Lee, John A. L. (Contributions to biblical exegesis and theology, 2022)
This volume brings together 28 of John Lee's most significant articles and book chapters published from 1969 to 2020. The papers are unified by a focus on ancient Greek language across a range of texts and dates. Many of the essays relate to the Septuagint, while the New Testament is the subject of others. Surveys of the state of Greek lexicography, reviews of lexicons,, and lexicographical studies feature strongly. Some essays cover topics such as the Atticist Grammarians; one takes a ground-breaking sociolinguistic approach to Mark's Gospel: and on discovers an early appearance of greek monotonic accentuation in the first edition of the Greek New Testament